Pengaruh penambahan lisin pada pakan komersil terhadap pertumbuhan, dan efisiensi pemanfaatan pakan benih ikan Nila (Oreochromis niloticus) - Yesi Maulina; Rustiana Widaryati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2020)
This study aims to analyze the effect of using lysine added to commercial feed on the growth of Tilapia (Oreochromis niloticus) seeds, and to determine the effective lysine dose to increase the growth and efficiency of feed utilization in Tilapia seeds. This research was conducted for 42 days of maintenance. The method used in this study is an experimental method. With a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used were the addition of 0 grams of lysine, 1.5 grams, 2 grams, and 2.5 grams to the feed. The results of this study were that the addition of lysine to commercial feed had a very significant effect on weight and length growth and feed conversion ratio, but did not affect EPP and SR of Tilapia seeds. Treatment C (2 grams of lysine) gave the best performance values in weight and length growth, and FCR of 7.13 grams, 3.67 cm, and 1.01 grams, respectively. The value of water quality parameters during the study was still within the tolerance range to support the life and growth of Tilapia seeds. Keywords : Lysine, growth, Tilapia, feed utilization.